The experiences in containment of the coronavirus epidemic on the Philippines: Interview with József Bencze, ambassador of Hungary in Manila (Academic Journal of Internal Affairs, 2020)
József Bencze, police lieutenant-general was director of the Hungarian Police Headquarters between 29th May 2007 and 30th June 2010. Between 2011 and 2016 he was the ambassador of Hungary in Skopje and from 2016 he has been ambassador in Manila. It might be a very special experience to follow everyday life of a foreign country as an inner observer and having up-to-date information as an ambassador. Even if there is everything in normal circumstances, there are always experiences rich on curiosities to get. And how is the situation in case of emerging extraordinary events?  How the ambassador of Hungary saw and experienced the spread of the coronavirus and the containment of that by the authorities on the Philippines?  Among others we asked Ambassador József Bencze about them, our questions were put by Csaba Szabó.
Keywords: coronavirus; extraordinary events; Manila